American Mosaic: Multicultural Readings in Context - Rico, Barbara Roche and Mano, Sandra (Boston Houghton Mifflin Company, 1991)
Explores and celebrates the pluralism of American culture by bringing together essays, stories and poems by members of nearly twenty ethnic and national groups. Exercises encourage students to develop their critical thinking skills.
Keywords: Reading